The impact of ICT on the efficiency of HRM in Cameroonian enterprises: Case of the Mobile telephone industry - Serge Mandiefe Piabuo; Ngwe Elvis Piendiah; Njoh Lawrence Njamnshi; Puatwoe Janice Tieguhong (Journal of Global Entrepreneurship Research, 2017)
The objective of this study is to determine the impact of Information and Communication Technology on the efficiency of Human Resource Management in the Cameroon mobile Telecommunication Sector. It specifically seeks to investigate how the use of ICT affects the following human resources management practices; Human resource planning, training and development, selection and recruitment, human resource evaluation and compensation. An exploratory research design was employed in the study. A sample of 120 management, senior, junior and contract staffs of the 03 (three) main mobile telephone operators responded to a structured questionnaire. The data collected was coded and entered into SPSS version 17. Pearson correlation coefficient was used to establish the relationship between the variables in the study, regression analysis was used to establish the combined effect of study variables on the dependent variable. The results show a significant positive relationship between the use of ICT in selection and recruitment, training and development, Human resource planning, evaluation and compensation and human resource management efficiency. This highlights the use of ICT as an efficient tool in Human resource management of enterprises. The use of ICT assures Human resource management efficiency, we therefore suggest that regular Information and Communication Technology training and development should be enhanced so as to allow proper interactions between Human Resource Management and the different departments which could lead to the organizational efficiency.
Keywords: 650; ICT; HRM; HR functions; HRM efficiency; ANOVA test; Telecommunication sector